2003
DOI: 10.4315/0362-028x-66.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Predictive Models for Growth of Parent and Green Fluorescent Protein–Producing Strains of Salmonella

Abstract: The green fluorescent protein (GFP) from the jellyfish Aequorea victoria can be expressed in, and used to follow the fate of, Salmonella in microbiologically complex ecosystems such as food. As a first step in the evaluation of GFP as a tool for the development of predictive models for naturally contaminated food, the present study was undertaken to compare the growth kinetics of parent and GFP-producing strains of Salmonella. A previously established sterile chicken burger model system was used to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 34 publications
5
30
1
Order By: Relevance
“…Three serotypes had growth on diced Roma tomatoes that was different from that of Salmonella Newport. The finding that growth among serotypes of Salmonella is mostly similar but on occasion differs is consistent with previous studies conducted in laboratory broth (Oscar, 1998), on cooked chicken without native microflora (Oscar, 2000(Oscar, , 2003, and on ground chicken with native microflora (Oscar, 2009(Oscar, , 2015.…”
Section: Discussionsupporting
confidence: 91%
“…Three serotypes had growth on diced Roma tomatoes that was different from that of Salmonella Newport. The finding that growth among serotypes of Salmonella is mostly similar but on occasion differs is consistent with previous studies conducted in laboratory broth (Oscar, 1998), on cooked chicken without native microflora (Oscar, 2000(Oscar, , 2003, and on ground chicken with native microflora (Oscar, 2009(Oscar, , 2015.…”
Section: Discussionsupporting
confidence: 91%
“…Taking this into account as well as the previous reports on cell toxicity of GFP E. coli O157:H7 (Fratamico et al 1997), Trichoderma harzianum (Bae and Knudsen 2000) and Salmonella spp. (Oscar 2003), it was important to determine the growth rate of the strain under the conditions of expressed and non-expressed gfpmut3 and compare this to the growth rate of the parental strain. No significant differences in growth rates were observed (Table 2).…”
Section: Construction Of E Coli Biosensor and Growth Characteristicsmentioning
confidence: 99%
“…Oscar et al [37] reported a 50 min lag phase extension of a Salmonella transformed strain which however, was not found significant. Oscar [38] also observed that constitutive expression of gfp altered growth characteristics of transformed Salmonella as the changes affected more growth rates and maximum population densities than lag times. In our study, however, L. innocua M1 transformation and gfp expression did not alter the growth rate which agreed with the reports of [39][40][41] for gfp-labeled Bordetella pertussis, Lactococcus lactis and E. coli K-12 strains respectively.…”
Section: Discussionmentioning
confidence: 92%